Enantioselective Synthesis of Cyclopropanone Equivalents and Application to the Formation of Chiral β‐Lactams. Issue 42 (18th August 2020) - Poteat, Christopher M.; Jang, Yujin; Jung, Myunggi; Johnson, J. Drake; Williams, Rachel G.; Lindsay, Vincent N. G.
Abstract: Cyclopropanone derivatives have long been considered unsustainable synthetic intermediates because of their extreme strain and kinetic instability. Reported here is the enantioselective synthesis of 1‐sulfonylcyclopropanols, as stable yet powerful equivalents of the corresponding cyclopropanone derivatives, by α‐hydroxylation of sulfonylcyclopropanes using a bis(silyl) peroxide as the electrophilic oxygen source. This work constitutes the first general approach to enantioenriched cyclopropanone derivatives. Both the electronic and steric nature of the sulfonyl moiety, which serves as a base‐labile protecting group and confers crystallinity to these cyclopropanone precursors, were found to have a crucial impact on the rate of equilibration to the corresponding cyclopropanone. The utility of these cyclopropanone surrogates is demonstrated in a mild and stereospecific formal [3+1] cycloaddition with simple hydroxylamines, leading to the efficient formation of chiral β‐lactam derivatives. Abstract : The first general approach to the formation of enantioenriched cyclopropanone equivalents is reported by the α‐hydroxylation of sulfonylcyclopropanes, giving access to a wide variety of highly reactive and modular reagents suitable for ring‐expansion processes. Exemplified here is the formation of chiral β‐lactams by a formal [3+1] cycloaddition using simple hydroxylamines as nitrene sources.